Desain dan Analisis Mesin Press Komposit Kapasitas 20 Ton - Muhammad Syaukani; Fajar Paundra; Fitrah Qalbina; Ilham Dwi Arirohman; Putty Yunesti; Sabar Sabar (Journal of Science, Technology, and Visual Culture, 2021)
Composite is a combination of several or more different materials, which produce better properties than their composition properties. The process of making composites can be done with a pressing method which can reduce voids. This pressing method can use a hydraulic press machine. This study aims to design and analyze a hydraulic press machine with a capacity of 20 tons. The design process begins with designing a 3D model using Solidwork Software. Numerical simulation using the finite element method by providing several variations in pressure loads ranging from 5-20 MPa. The results of the analysis show that the maximum von Mises stress is 79.70 MPa with a maximum deformation of 0.0176 mm and the smallest value of safety factor is 2.595. Based on these results, the press machine design is claimed to be safe to operate.